Young people with Type 1 diabetes of non‐white ethnicity and lower socio‐economic status have poorer glycaemic control in England and Wales. Issue 11 (23rd February 2016) - Khanolkar, A. R.; Amin, R.; Taylor‐Robinson, D.; Viner, R. M.; Warner, J. T.; Stephenson, T.
Abstract: Background: The impact of ethnicity and socio‐economic status (SES) on glycaemic control during childhood Type 1 diabetes is poorly understood in England and Wales. Methods: We studied 18 478 children with Type 1 diabetes (< 19 years) attending diabetes clinics and included in the 2012–2013 National Paediatric Diabetes Audit. Self‐identified ethnicity was categorized as white, Asian, black, mixed, other and 'not‐stated' (did not to divulge ethnicity). A small area measure of SES was estimated from the Index of Multiple Deprivation. Multiple linear regression was used to assess associations between ethnicity, SES and glycaemic control (mean HbA1c levels) accounting for age, gender and diabetes duration. The impact of insulin pump use on the ethnicity/SES–HbA1c associations was tested in 13 962 children. Results: All children from minority ethnic groups had higher mean HbA1c compared with white children, with largest differences observed in black and mixed ethnicities [8 mmol/mol (2.9%), 95% CI 5–11 and 7 mmol/mol (2.8%), 95% CI 5–9, respectively]. Lower SES was associated with higher mean HbA1c with a dose effect. The lowest SES group had a mean HbA1c that was 7 mmol/mol (2.8%) (95% CI 6–8) higher compared with the highest SES group, adjusted for ethnicity. Estimates for ethnicity were attenuated, but significant on adjustment for SES. Fewer non‐white (white 20.3 vs. black 5.5%) and deprived (least deprived 21.1 vs. most deprived 13.2%) children were on insulin pump therapy. Ethnicity and SES remained significant predictors of HbA1c after accounting for insulin pump use. Conclusion: The association between ethnicity and glycaemic control persists after adjustment for deprivation and pump use. An alternative approach to intensive insulin therapy might benefit these vulnerable children. What's new?: This is the largest study in the UK to investigate associations between ethnicity, deprivation and glycaemic control using a large nationally representative sample of children with Type 1 diabetes, from all major ethnic groups. Black and mixed ethnicity children had poorest glycaemic control. Greater deprivation was associated with worse glycaemic control in all ethnicities. Ethnicity remained independently associated with glycaemic control even after accounting for deprivation and treatment type (insulin pump therapy vs. no insulin pump therapy).